Verdenskrøniken 1812 læst igen - - Lundgreen-Nielsen, Flemming (Grundtvig-studier, 2013)
Verdenskrøniken 1812 som verdenslitteraturhistorie[The World Chronicle 1812 as a history of world literature]By Flemming Lundgreen-Nielsen Hidden in Grundtvig’s World Chronicle, 1812, is a history of world literature, infact the first published attempt of its kind written in Danish by a single scholar.This easily escapes attention as Grundtvig’s numerous paragraphs on poetry andliterary history are not marked typographically. This paper examines and discusses his most important statements chronologically. Even if Grundtvig’s brief portrayals of poets often describe a short bloom followed by rapid decay and an inevitablefall, he ends in foreseeing a renewal of Nordic literature led by Steffens, Oehlenschläger and himself. Thus Grundtvig, as early as 1812, introduces the Danish romantic breakthrough (1802 onwards) as a poetological paradigm which otherwise is first acknowledged by literary historians writing in the 1870s, ‘80s and ‘90s. Grundtvig’s survey of world literature has been overshadowed by more conspicuous and provocative qualities of his text but deserves a sober-minded consideration.